2004
DOI: 10.1021/cm048982k
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Defect Mechanisms in Cuprous Delafossites. 2. CuScO2and CuYO2

Abstract: The delafossite structure (ABO 2 ) accommodates a wide range of transition and rare-earth cations on the B-site in combination with a short list of A-site cations. This paper reports the effects on defect chemistry and transport as a function of the B-site cation in copperbased delafossite materials, with CuScO 2 and CuYO 2 as examples. Large B-site cation delafossites exhibit small polaron conduction, a diffusion-limited conduction mechanism, with an activation energy approximately twice that of CuAlO 2 (0.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 27 publications
(52 reference statements)
1
77
0
Order By: Relevance
“…79,80 In addition, delafossite structured materials have started to receive attention as potential electrodes in photoelectrochemical ͑PEC͒ water splitting, 65,[81][82][83][84][85][86][87][88] in spite of the fact that in many cases their band gaps are far in excess of the required range for PEC applications ͑1.7-2.2 eV͒. 89 It is clear from our results that due to the polaronic nature of these Cu I oxides, 69,70,90 effective mass theory is not an ideal way to rank the conductivity properties of delafossite materials. Further to this, calculating the natural valence band offsets for these ternary copper materials using the Wei and Zunger approach 74,75 does not yield any worthwhile information, and we have demonstrated that the trends are extremely sensitive to the choice of CL used in the analysis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…79,80 In addition, delafossite structured materials have started to receive attention as potential electrodes in photoelectrochemical ͑PEC͒ water splitting, 65,[81][82][83][84][85][86][87][88] in spite of the fact that in many cases their band gaps are far in excess of the required range for PEC applications ͑1.7-2.2 eV͒. 89 It is clear from our results that due to the polaronic nature of these Cu I oxides, 69,70,90 effective mass theory is not an ideal way to rank the conductivity properties of delafossite materials. Further to this, calculating the natural valence band offsets for these ternary copper materials using the Wei and Zunger approach 74,75 does not yield any worthwhile information, and we have demonstrated that the trends are extremely sensitive to the choice of CL used in the analysis.…”
Section: Discussionmentioning
confidence: 89%
“…33 It is clear from the results that we have obtained that applying effective mass theory to this type of material is not accurate. These systems do not have parabolic bands and have been shown experimentally in the cases of CuAlO 2 , 69 CuScO 2 , 70 and CuYO 2 ͑Ref. 70͒ to conduct via polaronic hopping mechanisms, which are not well described by effective mass theory.…”
Section: Effective Hole Masses Of the Vbmmentioning
confidence: 98%
“…Delafossites and Cu I oxides in general are considered to be polaronic, [53][54][55][56]58,70,96,[99][100][101][102][103][104][105][106] and as such it is expected that the CuCu distances should play a part in any conductivity, with holes expected to hop from Cu to Cu. 58 The Cu-Cu distance (equal to the a/b lattice constant) is determined by the size of the M III ion, which suggests that the conductivity will increase as the size of the M III ion decreases.…”
Section: Discussionmentioning
confidence: 99%
“…These results call into question the use of GGA/ LDA to model p-type defects in Cu(I) based TCOs, as the conductivity in these materials is known to be governed by polaronic-hopping mechanisms. [76][77][78] Indeed, this study represents the only ''beyond LDA/GGA'' study at present on defects in these technologically important materials, as all previous studies have utilised LDA/GGA to investigate the defects in SrCu 2 O 2 and Cu(I) based delafossites. 37,79,80 GGA + U produces distinct acceptor levels in the band gap for most of the defects, consistent with the activated conductivity noted experimentally.…”
Section: Discussionmentioning
confidence: 99%